SHAPING HIGHER EDUCATION: THE RISE OF ENTREPRENEURIAL UNIVERSITIES - Florina-Sanda TRIPA; Daniel BADULESCU; Alina BADULESCU; Simona-Aurelia BODOG (Business Excellence and Management)
Entrepreneurial universities play a crucial role in existing economic landscape, stimulating innovation, entrepreneurial initiative and economic development. These institutions extend their traditional mission of teaching and research by integrating an entrepreneurial perspective, promoting the commercialization of research and supporting start- ups. The concept of the entrepreneurial university has evolved significantly, now including actions and initiatives that support innovation and knowledge transfer to industry and communities. Factors such as visionary leadership, institutional culture, support networks and collaborations with business and public authorities are essential for the development of these universities. For regional development, knowledge transfer and commercialization of the academic research’s outcomes, the incubators and support for new firms are also important activities promoted by these universities. While facing challenges such as funding constraints and bureaucratic hurdles, entrepreneurial universities have significant opportunities to innovate and collaborate with industry partners. Their impact on regional development is evident by creating jobs, stimulating innovation and improving the local entrepreneurial ecosystem, thus contributing to economic growth and human capital development.